Pengaruh Pemberian Ekstrak Kulit Manggis Sebagai Stimulan Lateks Pada Tanaman Karet (Hevea Brasiliensis Muell. Arg.) - Yori Sulistia; Sari, Wulan Kumala; Warnita (Jurusan Budidaya Perkebunan, 2020)
Low productivity of para rubber trees in Indonesia can be anticipated by the application of technology in the downstream sector, especially in terms of tapping such as by the application of latex stimulants. The objectives of this study were to determine the effect of alternative stimulants sourced from household waste such as climacteric fruit peels that is mangosteen peel extract and obtain its concentration that gives the best effect on the latex production of rubber plants (Hevea brasiliensis Muell. Arg.). The reserach was carried out for five months at a smallholder rubber plantation in Dharmasraya District, West Sumatra. This study was designed using Randomized Block Design (RBD) that was repeated four times. The treatments were: without stimulant, mangosteen peel extract 3 ml application-1, mangosteen peel extract 4 ml application-1, mangosteen peel extract 5 ml application-1, and mangosteen peel extract 6 ml application-1. The results showed that the application of mangosteen peel extract as latex stimulants was able to increase the latex production when compared to without stimulant. Its application at 5 ml application-1 was able to produce the highest latex volume of 151,04 ml tapping-1 and without symptoms of tapping panel dryness.